2019
DOI: 10.1101/529065
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Incomplete influenza A virus genomes are abundant but readily complemented during spatially structured viral spread

Abstract: the frequency of co-infection and consequently reassortment are therefore likely to play an 53 important role in viral evolution. 54While the ability of a virus particle to enter a cell depends only on the proteins that line 55 the virion surface, subsequent production of viral progeny requires successful expression and 56 replication of the genome. A virion that does not contain, or fails to deliver, a complete genome 57 could therefore infect a cell but fail to produce progeny. IAV particles outnumber plaque… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
(54 reference statements)
0
9
1
Order By: Relevance
“…S4 for frequencies of individual genes). This measured frequency of infected cells expressing all eight genes is slightly higher than in our own prior work using the WSN strain (12) and slightly to substantially higher than that reported in studies by others using different viral strains or methodologies (15, 43, 61, 62).…”
Section: Resultscontrasting
confidence: 60%
See 1 more Smart Citation
“…S4 for frequencies of individual genes). This measured frequency of infected cells expressing all eight genes is slightly higher than in our own prior work using the WSN strain (12) and slightly to substantially higher than that reported in studies by others using different viral strains or methodologies (15, 43, 61, 62).…”
Section: Resultscontrasting
confidence: 60%
“…Despite the fact that we used a low-passage-number viral stock generated from plasmids, most infected cells did not express unmutated copies of all viral genes. Although our study is certainly not the first to note that influenza virus has a high mutation rate (3034) and sometimes fails to express genes (12, 15, 43, 61, 62), it is the first to directly observe the full spectrum of these defects across single cells. Visual inspection of Fig.…”
Section: Discussionmentioning
confidence: 92%
“…In co-infections between highly divergent parents, an inability to package any of the three segments results in attenuation, which has the potential to limit emergence of reassortant viruses. Conversely, only ∼1% of eight-segmented influenza A viruses replicate a full complement of segments within the infected cell, so co-infection is often necessary for successful completion of the viral life cycle 41 . As co-infected cells are the only ones capable of yielding reassortant progeny, a requirement for co-infection increases the likelihood that reassortment will occur.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the fact that 9S and 10S viruses can interfere with WT viral propagation strongly supports the notion that cellular co-infection is a common occurrence in vivo. Despite the historical notion that most viral particles are fully infectious, likely due to the fact that IAV particles package all eight genomic segments the majority of the time [59,60], recent work has suggested that co-infection may actually be not only a frequent occurrence that allows viral reassortment [61], but also a critical aspect of normal viral spread across infected tissues [62]. Since our 9S or 10S interfering effects are dependent on coinfection with WT viruses, we not only favor this model, but propose that even distinct viral infections that begin at different times are also subject to this co-infection phenomenon.…”
Section: Discussionmentioning
confidence: 99%